Nuclear magnetic resonance spectroscopy data of isolated compounds from Acacia farnesiana (L) Willd fruits and two esterified derivatives - Hernández García, Erika; García, Abraham; Avalos Alanís, Francisco Guadalupe; Rivas Galindo, Verónica Mayela; Delgadillo Puga, Claudia; Camacho Corona, María del Rayo (2019)
In the present article we describe the spectroscopic data of 1 H and 13C Nuclear Magnetic Resonance of 11 compounds including: Nine natural products from the hexanic-chloroformic and methanolic extracts of Acacia farnesiana fruit and two esterified derivatives (22E-stimasta5,22-dien- 3β-acetyl and methyl 3,4,5-triacetyloxybenzoate). Data linked to the research work entitled "Chemical composition of fruits of Acacia farnesiana (L) Willd and its activity against Mycobacterium tuberculosis and dysentery bacteria" (Hernández et al., 2019) [1]. & 2018 The Authors. Published by Elsevier Inc. This is an open access article under the CC BY license